USP13 regulates HMGB1 stability and secretion through its deubiquitinase activity - Jaemin Shin; Young Hun Kim; Bin Lee; Jae Ho Chang; Hee Youn Choi; Hoojung Lee; Ki Chan Song; Man Sup Kwak; Ji Eun Choi; Jeon-Soo Shin (BMC, 2022)
Abstract Background High mobility group box 1 (HMGB1) is a damage-associated molecular pattern (DAMP) molecule that plays a central role in innate immunity. HMGB1 acts as a late mediator of inflammation when actively secreted in response to inflammatory stimuli. Several post-translational modifications (PTMs), including acetylation, phosphorylation, and oxidation, are involved in HMGB1 secretion. However, the E3 ligases of HMGB1 and the mechanism by which DUBs regulate HMGB1 deubiquitination are not well known. Methods LC-MS/MS, proximity ligation assay, immunoprecipitation were used to identify ubiquitin-specific protease 13 (USP13) as a binding partner of HMGB1 and to investigate ubiquitination of HMGB1. USP13 domain mutant was constructed for domain study and Spautin-1 was treated for inhibition of USP13. Confocal microscopy image showed localization of HMGB1 by USP13 overexpression. The data were analyzed using one-way analysis of variance with Tukey's honestly significant difference post-hoc test for multiple comparisons or a two-tailed Student's t-test. Results We identified ubiquitin-specific protease 13 (USP13) as a novel binding partner of HMGB1 and demonstrated that USP13 plays a role in stabilizing HMGB1 from ubiquitin-mediated degradation. USP13 overexpression increased nucleocytoplasmic translocation of HMGB1 and promoted its secretion, which was inhibited by treatment with Spautin-1, a selective inhibitor of USP13. Conclusion Taken together, we suggest that USP13 is a novel deubiquitinase of HMGB1 that regulates the stability and secretion of HMGB1.